Hadron masses from a Kaluza-Klein like Model - Vieten, Manfred (My University, 2021)
The Standard Model of particle physics is re-interpreted in terms of Kaluza-Klein theory. In this paper, a model consisting of 10 dimensions is presented which are: one time, three usual macroscopic space and six compactified dimensions. Excitations - disturbances traveling with the speed of light on the 10D space-time - are introduced. An excitation on a compactified dimension induces a mass in 4D space-time; it is accompanied by an integer, the excitation number, and has a well-defined spin. The model’s free parameters are computed using the measured masses of the leptons, including the upper bound of the mass difference between electron and positron, the mesons π0, π+, ρ0, ϕ, ψ, Υ, the top-quark mass, and the magnetic moment of the electron. The most important parameters are the compactification radius ρ, the weak coupling αw, the strong coupling αs and the anti-neutrino to neutrino density ratio δ. The formulas for calculating hadron masses are given and applied to approximately one hundred composite particles, which are compiled within four separate tables. The comparison between the measurement and calculation shows the relative errors mostly below 0.05. δ appears to deviate marginally from one, which points towards slightly different densities when comparing anti-neutrinos to neutrinos.
Keywords: Kaluza-Klein theory, geodesic equation, hadron masses, Standard Model, anti- neutrino/neutrino density, neutrino mass; 530